2010
DOI: 10.1017/s0007114510002217
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modulation of 4E binding protein 1 (4E-BP1) phosphorylation by watercress: a pilot study

Abstract: Dietary intake of isothiocyanates (ITC) has been associated with reduced cancer risk. The dietary phenethyl ITC (PEITC) has previously been shown to decrease the phosphorylation of the translation regulator 4E binding protein 1 (4E-BP1). Decreased 4E-BP1 phosphorylation has been linked to the inhibition of cancer cell survival and decreased activity of the transcription factor hypoxia-inducible factor (HIF), a key positive regulator of angiogenesis, and may therefore contribute to potential anti-cancer effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Rowland and colleagues have demonstrated reduced levels of basal and hydrogen peroxide-induced DNA damage in peripheral blood lymphocytes, presumably due to Nrf2-dependent increased antioxidant gene expression, following daily intake of 85 g of watercress for 8 weeks [75]. Our own pilot work has shown that ingestion of watercress (80 g) appears to be sufficient to cause a transient decrease in 4E-BP1 phosphorylation [73] mirroring effects seen in vitro in cancer cells [31,33]. Moreover, ingestion of SFN-enriched broccoli sprouts is associated with inhibition of HDAC activity and accumulation of acetylated histone [76] Isothiocyanates and angiogenesis -18 -will determine the tolerability and toxicity of oral intake of SFN-enriched broccoli sprout extract in patients with invasive transitional cell carcinoma of the bladder (with secondary aims to study the effects on tumour angiogenesis, cell proliferation and apoptosis).…”
Section: Relevance For Chemoprevention and Chemotherapymentioning
confidence: 85%
See 1 more Smart Citation
“…Rowland and colleagues have demonstrated reduced levels of basal and hydrogen peroxide-induced DNA damage in peripheral blood lymphocytes, presumably due to Nrf2-dependent increased antioxidant gene expression, following daily intake of 85 g of watercress for 8 weeks [75]. Our own pilot work has shown that ingestion of watercress (80 g) appears to be sufficient to cause a transient decrease in 4E-BP1 phosphorylation [73] mirroring effects seen in vitro in cancer cells [31,33]. Moreover, ingestion of SFN-enriched broccoli sprouts is associated with inhibition of HDAC activity and accumulation of acetylated histone [76] Isothiocyanates and angiogenesis -18 -will determine the tolerability and toxicity of oral intake of SFN-enriched broccoli sprout extract in patients with invasive transitional cell carcinoma of the bladder (with secondary aims to study the effects on tumour angiogenesis, cell proliferation and apoptosis).…”
Section: Relevance For Chemoprevention and Chemotherapymentioning
confidence: 85%
“…Pharmacokinetic studies have demonstrated that ITCs are detectable in the blood following ingestion of cruciferous vegetables, but these levels would appear to fall short of those required for modulation of angiogenesis pathways. For example, in two studies, the mean peak plasma concentrations of PEITC following ingestion of 80 or 100 g of watercress were 297 and 928 nM, respectively [72,73]. The mean peak plasma concentration of SFN following ingestion of 150 ml of broccoli "soup" equivalent to 100 g of broccoli was ~650 nM [74].…”
Section: Relevance For Chemoprevention and Chemotherapymentioning
confidence: 99%
“…For example, the inhibitory effects of watercress on the oxidative metabolism of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone in the peripheral blood cells of participants have been described [117]. Similarly, a randomized and placebo-controlled trial utilizing a beverage infused with broccoli sprouts exhibited an inverse association between the excretion of dithiocarbamates and urinary aflatoxin-DNA adducts [118].…”
Section: Dietary Glucosinolate Derivatives: In Vivo Studiesmentioning
confidence: 99%
“…Watercress is the richest source of the natural antioxidant compound, Phenyl Ethyl Isothiocyanate (PEI), being able to stop the function of a protein called Hypoxia Inducible Factor (HIF) playing a vital role in cancer development [11]. Cancer cells develop if they obtain enough oxygen and nutrients to maintain the growth.…”
Section: Watercress (Rorripa Nasturtium Aquaticum)mentioning
confidence: 99%